Impact of delayed cord clamping and minimally invasive surfactant administration on outcomes in premature infants with neonatal respiratory distress syndrome at less than 30 weeks gestation: a NICU quality improvement study - Zhang, Yijia; Zhang, Hui; Zhang, Yahui; Li, Xinyue; Yan, Zheng; Zhang, Jinghui; Zhang, Hua; Piao, Meihua; Han, Tongyan (Frontiers in Pediatrics, 2025)
BackgroundPreventing early invasive mechanical ventilation (IMV) in preterm infants is critical for reducing bronchopulmonary dysplasia (BPD) and improving outcomes. While delayed cord clamping (DCC) enhances cardiopulmonary stability and minimally invasive surfactant administration (MISA) reduces IMV dependence, evidence on their combined efficacy in extremely preterm infants (<30 weeks gestation) with neonatal respiratory distress syndrome (NRDS) remains limited. We hypothesize that integrating DCC with MISA will synergistically reduce BPD incidence compared to immediate cord clamping (ICC) with either MISA or tracheal intubation-based surfactant delivery.Methods and designThis is a single-center quality improvement study evaluating three treatment regimens for neonates with NRDS born at a gestational age of <30 weeks: (1) Retrospective data collection of cases treated with the conventional approach of ICC + tracheal intubation between 2017 and 2020 (n = 222); (2) Retrospective data collection of cases treated with ICC + MISA between 2021 and 2025 (n = 222); (3) Planned collection of medical records of cases treated with DCC + MISA between 2025 and 2027 (n = 74).The study aims to assess the incidence of BPD and survival outcomes associated with each regimen. Meanwhile, it will compare the short-term efficacy, safety, and long-term outcomes of these three treatment strategies, thereby providing valuable evidence for clinical treatment decision-making.DiscussionCurrent research indicates that both DCC and MISA positively impact the prognosis of very premature infants and help reduce the incidence of BPD. However, there is limited research on whether the combined use of DCC and MISA can further improve survival rates and reduce the incidence of BPD in this vulnerable population. Our NICU has gradually implemented MISA in respiratory management since 2021 and adopted cord management with DCC since 2025. This study retrospectively analyzes data from previous groups: those receiving ICC with MISA, and those receiving ICC with tracheal intubation. We will compare this with prospective data from the DCC combined with MISA group to assess differences in BPD occurrence, other complications and overall outcomes. This study will also collect and analyze the annual application rates and operational success rates of MISA and DCC, so as to promote quality improvement in the NICU. Through this study, we aim to determine whether the combination of DCC and MISA offers greater benefits in improving the prognosis of very premature infants, ultimately providing a stronger foundation for early respiratory and circulatory management strategies for infants born before 30 weeks.Trial Registrationhttps://register.clinicaltrials.gov, Identifier:NCT07092319.